The basic biology of NK cells and its application in tumor immunotherapy - Jiang, Pan; Jing, Shaoze; Sheng, Gaohong; Jia, Fajing (Frontiers in Immunology, 2024)
Natural Killer (NK) cells play a crucial role as effector cells within the tumor immune microenvironment, capable of identifying and eliminating tumor cells through the expression of diverse activating and inhibitory receptors that recognize tumor-related ligands. Therefore, harnessing NK cells for therapeutic purposes represents a significant adjunct to T cell-based tumor immunotherapy strategies. Presently, NK cell-based tumor immunotherapy strategies encompass various approaches, including adoptive NK cell therapy, cytokine therapy, antibody-based NK cell therapy (enhancing ADCC mediated by NK cells, NK cell engagers, immune checkpoint blockade therapy) and the utilization of nanoparticles and small molecules to modulate NK cell anti-tumor functionality. This article presents a comprehensive overview of the latest advances in NK cell-based anti-tumor immunotherapy, with the aim of offering insights and methodologies for the clinical treatment of cancer patients.